The Heritage of Ghanaian Traditional Furniture Culture - Paul Benedict Inkum; Obed Persie Appiah-Kubi; Jiufang Lu; Zhihui Wu (Newinera Publisher, 2021)
Traditional Ghanaian furniture designs are known as an exhibition of the splendor and elegance of decorative objects or decorative ornaments that carry profound philosophical and sacred meanings. The features found in Ghana’s traditional Ghanaian design can be considered as objects for international players, with their own identity and not found elsewhere. This paper therefore seeks to identify and illuminate some of these Akan cultural objects in Ghana by referring to the Ashanti region. This paper also shows with examples how these design elements can be developed and maintained by integrating them into modern furniture and interior designs or as a straightforward or adaptive design.